Influência da vagotomia gástrica proximal sobre a zona de alta pressão esofagogástrica do cão. - Henry, M. A.; Leite, C. V.; Mendes, E. F.; Vercesi, L. A.; Lucchiari, P. H. (My University, 1988)
The influence of parietal cell vagotomy (PCV) on esophagogastric high pressure zone (HPZ) (pressure and length) was studied in 30 dogs. The animals were divided in 3 groups: group 1, 10 dogs submitted to PCV with gastric denervation until the esophagogastric junction; group 2, 10 dogs submitted to PCV with gastric denervation into esophagogastric junction and 3 cm above this; group 3 (control), 10 dogs submitted to laparotomy only. In the postoperative period (immediate and later) it wasn't observed any alteration of pressure and length of esophagogastric HPZ in three studied groups.
Influence of proximal gastric vagotomy on the esophageal high pressure zone in dogs
Keywords: animal; denervation; dog; highly selective vagotomy; lower esophagus sphincter; male; manometry; pathophysiology; pressure; Animal; Denervation; Dogs; English Abstract; Esophagogastric Junction; Male; Manometry; Pressure; Vagotomy, Proximal Gastric